Praying to the Temple : Divine Presence in Solomon's Prayer. - Wilson, I. (Leuven : Peeters Publishers & Booksellers, 2022)
There is a long-standing consensus that Solomon's prayer in 1 Kings 8 characterizes YHWH as having been 'relocated' to heaven and therefore no longer present in the temple. This study is the first sustained attempt to challenge that view. It does so by focusing on a hitherto overlooked collocation within the chapter, and concludes that the prayer portrays YHWH as being present both in heaven and in the building. Such a finding inevitably has consequences for wider issues involving divine presence both within and beyond the confines of 1 Kings 8. These include a cluster of ideas traced to the large central section of the chapter and involving a purely transcendent Deity, a (semi-)independent divine "name" inhabiting the sanctuary and an effectively desacralized temple. All three, together with the scholarly construct known as Name Theology, are called into question if YHWH is indeed represented as being localized within the temple.
Description based upon print version of record.
JSTOR
Keywords: Temple of Jerusalem (Jerusalem) -- In the Bible; Bible. -- Criticism, interpretation, etc; Temple of Jerusalem (Jerusalem); Presence of God; Présence de Dieu; RELIGION / Biblical Criticism & Interpretation / Old Testament; Presence of God; Temple of Jerusalem (Jerusalem) in the Bible; Electronic books; Criticism, interpretation, etc